Islamic Legal Modernism and Women’s Rights in Indonesian Pesantren Communities - Mahira Aluna Prameswari (The Indonesian Journal of Islamic Legal Modernism, 2026)
The discourse on women’s rights has become an increasingly important dimension of Islamic legal development in Indonesia, particularly within pesantren communities that play a central role in religious education and social transformation. This study examines the relationship between Islamic legal modernism and the advancement of women’s rights in Indonesian pesantren communities. Employing a normative and sociolegal approach, the research analyzes contemporary interpretations of Islamic teachings concerning gender equality, education, leadership, and social participation. The findings indicate that many pesantren institutions have increasingly embraced reform-oriented interpretations that support broader opportunities for women while remaining grounded in Islamic principles. Islamic legal modernism has facilitated critical engagement with classical jurisprudential traditions, enabling reinterpretations that emphasize justice, dignity, and equal human worth. The study further reveals that women scholars, religious educators, and community leaders play a significant role in promoting gender-sensitive understandings of Islamic law. Nevertheless, challenges remain due to varying cultural norms, institutional traditions, and differing interpretations of religious authority. The research argues that Islamic legal modernism provides an important intellectual framework for reconciling religious authenticity with contemporary human rights concerns. Through contextual interpretation and renewed legal reasoning, pesantren communities contribute to the evolution of Islamic legal discourse on gender issues in Indonesia. The study concludes that the advancement of women’s rights within pesantren reflects the dynamic capacity of Islamic law to respond to social change while preserving its ethical foundations. These findings contribute to broader debates on gender, Islamic education, and legal modernization in contemporary Muslim societies.